Pengaruh Pemberian Ekstrak Peperomia pellucida Terhadap Penurunan Ekspresi Tumor Necrosis Factor Alpha (TNF-α) Pada Ginjal Tikus Wistar Jantan Yang Mendapat Pajanan Asap rokok - Nerawati, Maria Fransiska; Farida Anggraini Soetedjo; Heru Setiawan (Calvaria Medical Journal, 2024)
Introduction: Exposure to cigarette smoke causes oxidative stress and inflammatory responses through free radicals. Tumor Necrosis Factor Alpha is a pro-inflammatory cytokine that exacerbates kidney inflammation. The administration of exogenous antioxidants and anti-inflammatory agents is expected to prevent kidney injury caused by cigarette smoke exposure. Peperomia pellucida, also known as "sirih cina," is a plant known for its antioxidant and anti-inflammatory activities. This study aims to investigate the effect of Peperomia pellucida extract on the reduction of TNF-α expression in the kidneys of male Wistar rats exposed to cigarette smoke.Methods: This true experimental study used a post-test only control group design with male Wistar rats aged 8-12 weeks, obtained from the Experimental Animal Laboratory of the Faculty of Medicine, Wijaya Kusuma University, Surabaya. The sample consisted of 20 rats meeting the inclusion and exclusion criteria, with a body weight of approximately 180-200 grams. Data were analyzed using the Mann-Whitney test.Results: The Mann-Whitney test showed a significant difference between groups P1 and P2, with a significance value of 0.025. This indicates that the administration of Peperomia pellucida extract significantly reduced TNF-α expression in the kidneys of rats exposed to cigarette smoke.Conclusion: Administration of Peperomia pellucida extract at a dose of 400 mg/kg/day can reduce TNF-α expression in the kidneys of male Wistar rats exposed to cigarette smoke.